Understanding the Factors that Influence User Adoption and Intention to Recommend the E-health Apps In Indonesia - Ferdi Antonio (Journal of International Conference Proceedings (JICP), 2018)
E-health through the mobile application is an emerging technology that could disrupted health care industry chain from the traditional way. This e-health apps in mobile device provides more accessible and convenient health-related services while offers social economic values as well. however the market potential have not followed yet by the representative of e-health apps penetration while the study on how this technology adopted among customer were limited. This study aims to investigate the customer behaviour in regard of customer adoption intention of the e-health app. This study focuses on identifying the influential factors of customer adoption based on unified theory of adoption and use of technology (UTAUT 2) with diffusion of innovation (DOI) frame work added by perceived security and price promotion variable. The study empirically tested to 160 eligible samples who have been used the two most downloaded health service apps in Indonesia. The primary data were collected by online survey through Likert scale questionnaire and analyzed by SEM PLS. The result indicate that key factors in customer adoption are perceived usefulness, perceived ease of use, price value and price promotion which shown significant effect, while the rest factors were discussed. This study offers insights for e-health apps developers on how to optimally design and promote the apps product by consider customer adoption process which would convert to their intention to recommend. Further research across socio-demography is needed to confirm this finding. Keywords: e-health apps, UTAUT2, price promotion, customer adoption, intention to recommend